Traditional Games as Therapeutic Interventions: Enhancing Socio-Emotional Development of Children with ADHD in Inclusive Kindergarten Settings - Sujariah, Sujariah; Azizah, Nur (Papanda Publisher, 2025)
Socio-emotional development challenges in children with ADHD represent a critical area requiring targeted intervention, particularly within inclusive early childhood education settings. Traditional games offer culturally relevant therapeutic potential, yet limited empirical research exists examining their specific application for children with attention deficit disorders in Indonesian educational contexts. This study investigated the effectiveness of traditional games in enhancing socio-emotional development of children with ADHD in inclusive kindergarten settings. A classroom action research design following the Kemmis and McTaggart model was implemented across two cycles at a public kindergarten in Muara Wahau District, East Kutai Regency. Participants included 30 students in class B4, with particular focus on one child diagnosed with ADHD. Data collection utilized structured observation checklists measuring three domains: self-awareness, responsibility, and prosocial behavior. Traditional Indonesian games including Gobak Sodor, Ular Naga Panjang, Cublek-Cublek Sugeng, Petak Umpet, ABC Lima Dasar, and Tikus dan Kucing were systematically implemented. Overall success rates improved significantly from 64% in the pre-cycle phase to 84% in Cycle II, exceeding the predetermined 75% success criterion. The child with ADHD demonstrated remarkable progress, with social-emotional competency scores increasing from 25% to 50%, meeting the established 50% improvement criterion for children with attention deficit disorders. Substantial reductions occurred in the